Mechanics of Soft Materials - Volokh, Konstantin (Springer Nature Singapore : Imprint: Springer, 2019)
This book provides a concise introduction to soft matter modelling, together with an up-to-date review of the continuum mechanical description of soft and biological materials, from the basics to the latest scientific materials. It also includes multi-physics descriptions, such as chemo-, thermo-, and electro-mechanical coupling. The new edition includes a new chapter on fractures as well as numerous corrections, clarifications and new solutions. Based on a graduate course taught for the past few years at Technion, it presents original explanations for a number of standard materials, and features detailed examples to complement all topics discussed.